MARKET BASED CAPABILITIES AND RESULTS: INFERENCE FOR TELECOMMUNICATION SERVICE BUSINESSES IN NIGERIA - Olufemi Amos, Akinbola; Omotayo Adeniyi, Adegbuyi; Bisayo Oluwatosin, Otokiti (European Scientific Journal, ESJ, 2014)
This research is aimed at measuring the effect of market based capabilities on corporate result. The objectives of the study were to determine the relationship between market capabilities and market share, the relationship between information technology and productivity, and the relationship between customer relationship management and brand loyalty. Series of questions were asked using the questionnaire adopted by the research and three hypotheses were proposed and tested in the study. To determine the capabilities and organization performance, a sample of 100 consumers and 50 employees were drawn respectively. The data was analyzed using simple frequency tables, regression analysis and Pearson product moment correlation. Finally, the analysis shows that market capabilities has a large influence on organizational performance in its industry. Based on the above findings, there is need for organizations to recognize their capabilities that will ensure organization performance.